O ensino da história e cultura afro-brasileira na óptica do coordenador pedagógico - Ignácio, Vera Balbino da Silva (2008)
This research s aim is to study, from the pedagogical coordinator teacher s point of view, the teaching of African-Brazilian History and Culture subject, recently included in the curriculum of the state primary and secondary public schools Law 10.639/03 , which modifies the LDBN 9.394/06 Law of Guidelines and Bases of the National Education Lei de Diretrizes e Bases da Educação Nacional. The main objective was to verify the pedagogical coordinator s comprehension towards the legal statements of the Law 10.639/03, that is, the ethnic-racial debate in the school context. Therefore, we intended to relate the coordinator s view about the possibilities and limits in the pedagogical treatment of the African matrix teaching, referring to the fulfillment of this legal mechanism. It is exploratory research that took place in a regional teaching directorship in the city of São Paulo. The data was collected from the anti-racism federal educational law and by means of questionnaire referring to African-Brazilians demands, culture and history answered by ten coordinators who had agreed to take part in the research. In order to analyze the articulation between the educational laws, pedagogical practices and racial relationships, concepts from the Critical Theory were chosen as theoretical reference, especially in relation to the analysis of prejudice, which aroused during the research procedures. After the data collection, we realized there was no straight relation between the coordinator s speech and practice because we could notice on their speech an apparent harmony that did not fit the subtle prejudice which does not allow them to break the barrier of invisibility before important aspects that characterize the multicultural education. This conclusion indicates that the possibilities brought by the educational law must be accompanied by social, educational, and individual conditions that are being built